A novel sequence of the PHKG 2 mutation associated with the first case of glycogen storage diseases type IXc in Syria: a case report and review of literature - Seba Harh; Shaza Shahoud; Shady Daher; Diana Alasmar (Journal of Medical Case Reports)
Abstract Background Glycogen storage diseases are a group of inherited metabolic disorders that affect the body’s ability to break down and/or store glycogen. Type IX glycogen storage disease is an inherited disorder caused by a deficiency of phosphorylase kinase, which leads to various symptoms. We report the first reported case in Syria of glycogen storage disease type IXc caused by a novel phosphorylase B kinase catalytic subunit gamma 2 gene mutation, emphasizing the importance of early diagnosis and genetic counseling. Case presentation A 6-month-old Syrian male infant of Arab ethnicity presented with developmental delay, hepatomegaly, and hypoglycemia. Genetic testing identified a previously unreported phosphorylase B kinase catalytic subunit gamma 2 variant (c.801G > A p.( =)), classified as a variant of uncertain significance. Liver biopsy and clinical features were consistent with glycogen storage disease type IXc. Discussion This report expands the current understanding of phosphorylase B kinase catalytic subunit gamma 2-related glycogen storage disease type IXc by documenting a novel synonymous mutation with potential clinical significance. It underscores the critical role of early genetic testing in consanguineous populations, not only for accurate diagnosis but also for guiding family counseling and long-term management. Conclusion The identification of this novel mutation contributes to expanding the known phosphorylase B kinase catalytic subunit gamma 2 mutation spectrum and stresses the need for genetic counseling in similar populations.